PENGARUH PROMOSI JABATAN DAN HUBUNGAN INTERPERSONAL TERHADAP KINERJA PEGAWAI PT. KERETA API INDONESIA (PERSERO) DIVRE II SUMATERA - Dian Kumala Sari, Yusnaena , Syahrul Effendy (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2016)
This study , entitled the effect of promotion and interpersonal relationships to employeeperformance PT Kereta Api West Sumatra Regional Division II. This study was toexamine the effect of interpersonal danhubungan promotion to employee performance PTKereta Api Indonesia. (Persero) Division II of West Sumatera. This study is a survey withquantitative approach, which aims to determine the effect of promotion and interpersonalrelationships on employee job satisfaction PT. Kereta Api. The data used are primary dataobtained by field survey. Hypothesis testing is done by means of multiple regressionanalysis The study population was all all employees at PT Kereta Api numbering 87 peopleand all of them were sampled by taking total sampling technique. Data collectiontechniques in this study conducted by survey method. Using two instrument consists ofthree devices questionnaire for the study variables with the results of the study are positiveand significant influence between promotion jabata to the performance on PT. Kereta ApiIndonesia (Persero) Division II West Sumatera with a regression coefficient of 0.478 witha significant level of 0.000 < 0.05. There is a significant relationship between interpersonalrelationship to the performance on PT. Kereta Api Indonesia (Persero) Division II WestSumatera with a regression coefficient of 0.374 with a significant level of 0.002 < 0.05Keywords: Promotions, interpersonal relations and promotions